Simulation of charring depth of timber structures when exposed to non-standard fire curves. (22nd June 2017) - Mindeguia, Jean-Christophe; Cueff, Guillaume; Dréan, Virginie; Auguin, Gildas
Abstract : Purpose: The fire resistance of wooden structures is commonly based on the calculation or measurement of the char layer. Designers usually estimate the char layer at the surface of a structural element by using analytical models. Some of these charring models can be found in regulations, as Eurocode 5. These analytical models, quite simple to use, are only reliable for the standard fire curve. In that case, the design of the structure is qualified as "prescriptive-based design" and can lead to oversizing the structure. Optimization of a structure can be achieved by using a "Performance-based design", where realistic fire scenarios are taken into account by means of more or less complex models [parametric fires, two-zones models, computational fluid dynamics (CFD)]. For these so-called "natural fires", no model for charring is available. The purpose of this paper is to present a novel methodology for applying a performance-based design to a simple timber structure. Design/methodology/approach: This paper presents the development of a numerical model aiming to simulate the thermal transfer and charring in wood, under any type of thermal exposure, including non-standard fire curves. After presenting the physical background, the model is calibrated and compared to existing experimental studies on wood samples exposed to different fire curves. The model is then used as a tool for assessing the fire resistance of a common wooden structure exposed to standard and non-standard fire curves. Findings: The results show that the fire resistance is obviously dependent on the choice of the thermal exposure. The reliability of the model is also discussed and the importance of taking into account particular reactions in wood during heating is underlined. Originality/value: One aim of this paper is to show the opportunity to apply a performance-based approach when designing a wooden structure. It shows that more knowledge of the material behaviour under non-standard fires is still needed, especially during the decay phase.